Effect of cathode composition on microstructure and tribological properties of TiBN nanocomposite multilayer coating synthesized by plasma immersion ion implantation and deposition - Lü, Wen-quan; Cao, Yong-zhi; Wang, Lang-ping; Wang, Xiao-feng; Gu, Zhi-wei; Yan, Yong-da; Yu, Fu-li (Journal of Central South University, 2017)
Nanocomposite multilayer TiBN coatings were prepared on Si (100) and 9Cr18Mo substrates using TiBN composite cathode plasma immersion ion implantation and deposition technique (PIIID). Synthesis of TiBN composite cathodes was conducted by powder metallurgy technology and the content of hexagonal boron nitride (h-BN) was changed from 8% to 40% (mass fraction). The as-deposited coatings were characterized by energy dispersive spectrometer (EDS), grazing incidence X-ray diffraction (GIXRD), Fourier Transform Infrared Spectroscopy (FTIR) and high resolution transmission electron microcopy (HRTEM). EDS results show that the B content of the coatings was varied from 3.71% to 13.84% (molar fraction) when the composition of the h-BN in the composited cathodes was changed from 8 % to 40% (mass fraction). GIXRD results reveal that the TiBN coatings with a B content of 8% has the main diffraction peak of TiN (200), (220) and (311), and these peaks disappear when the B content is increased. FTIR analysis of the multilayer coatings showed the presence of h-BN in all coatings. TEM images reveal that all coatings have the characteristics of self-forming nanocomposite multilayers, where the nanocomposites are composed of face-centered cubic TiN or h-BN nanocrystalline embedded in amorphous matrix. The tribological tests reveal that the TiBN coatings exhibit a marked decrease of coefficient at room temperature (~0.25). The improved properties were found to be derived from the comprehensiveness of the self-forming multilayers structure and the h-BN solid lubrication effects in the coatings.